A retrospective cohort study of low-dose intensity-modulated radiotherapy for unresectable liver metastases. Issue 4 (October 2020) - Pei, Su; Chen, Kaihua; Yang, Yunli; Chen, Long; Zhu, Xiaodong
Objective: To evaluate the efficacy and toxicity of intensity-modulated radiotherapy (IMRT) for the treatment of unresectable liver metastases. Methods: Twenty-five patients with unresectable liver metastases treated with IMRT were enrolled from January 2003 to September 2016. The median longest diameter of the lesions was 3.3 cm (range, 1.6–16.7 cm). The fraction dose ranged from 2 to 5.2 Gy, with a median total dose of 50 Gy (range, 30–60 Gy). Results: The median follow-up was 9.2 months (range, 2.1–48.8 months). The overall survival rates at 1 and 2 years were 46.4% and 27.4%, respectively. The 1-year local control rate was 69.8%. The 1-year progression-free survival rate was 26.3%. One patient had grade 4 liver dysfunction. One case of grade 4 leukopenia and one case of grade 3 leukopenia occurred, and one case of grade 3 leukopenia and thrombocytopenia was observed. Conclusion: IMRT may be a promising and safe treatment for unresectable liver metastases and can be used as a treatment option.